Public Administration in Developing Countries: Mediating the Internalisation of Global Legal and Policy Frameworks of the SDGs - Hasan, Syahrul; Taufiqurokhman, Taufiqurokhman; Satispi, Evi; Andriansyah, Andriansyah; Malik, Syaibatul Hamdi (Sinthop: Media Kajian Pendidikan, Agama, Sosial dan Budaya, 2025)
This article examines the role of public administration in developing countries in internalising global legal and policy frameworks associated with the Sustainable Development Goals. The study employs a narrative literature review to synthesise research on administrative capacity, legal adaptation, and the influence of global political processes on national development strategies. The review shows that public administration provides the institutional means through which global commitments are interpreted and embedded in domestic policy. The ability of governments to coordinate sectoral institutions, manage information systems, and align national regulations with international norms shapes how far the SDGs can be translated into practical action. The literature also highlights variations in governance quality, regulatory coherence, and enforcement practices that influence the internalisation process. Global political developments such as development assistance and international monitoring further shape national responses, although their impact depends on the stability and capability of domestic administrative systems. The findings indicate that improvements in coordination, legal consistency, and accountability are important steps toward narrowing the gap between global frameworks and national implementation. These insights offer a conceptual foundation for understanding the institutional conditions that affect SDG progress in developing countries.